Case study on bridge approach settlement and preventive measures by piled raft foundation [electronic resource] - 292369 Katiravan Moorthi; Fakulti Kejuruteraan Awam (2007)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2007